1956
DOI: 10.1039/jr9560003006
|View full text |Cite
|
Sign up to set email alerts
|

583. Preparation, stability, and complex formation of aryloxyboron compounds

Abstract: A number of triaryl borates have been prepared by interaction of boron trichloride and the phenol or naphthol, and steric and polar factors concerning their amine addition compounds are discussed. Ammonia forms 3 : 1 and 2 : 1 complexes respectively with tris-2 : 4 : 6-trichlorophenyl and triphenyl borate. Whereas P-nitrophenyl, o-tolyl, and o-chlorophenyl dichloroboronite are unstable, o-nitrophenyl dichloroboronite is by cornparison remarkably stable, a property ascribed to internal co-ordination ; but all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

1958
1958
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Der gebildete Dichlorborsaure-arylester konnte selbst noch als Lewissaure (vgl. [42]) die Umlagerung von Allyl-phenylather einleiten. Auf der anderen Seite ist bekannt , dass vergleichbare Dichlorborsaureester leicht in Chlorborsaurediarylester und Bortrichlorid disproportionieren konnen [42].…”
Section: Neuerdings Hat Miller R361 Bei Der Einwirkung Von Methanolisunclassified
See 1 more Smart Citation
“…Der gebildete Dichlorborsaure-arylester konnte selbst noch als Lewissaure (vgl. [42]) die Umlagerung von Allyl-phenylather einleiten. Auf der anderen Seite ist bekannt , dass vergleichbare Dichlorborsaureester leicht in Chlorborsaurediarylester und Bortrichlorid disproportionieren konnen [42].…”
Section: Neuerdings Hat Miller R361 Bei Der Einwirkung Von Methanolisunclassified
“…[42]) die Umlagerung von Allyl-phenylather einleiten. Auf der anderen Seite ist bekannt , dass vergleichbare Dichlorborsaureester leicht in Chlorborsaurediarylester und Bortrichlorid disproportionieren konnen [42]. Eine Zuni Schluss sei noch auf den speziellen ccfJara-Effekt H eingegangen, der bei cler Umlagerung von a-Methylallyl-arylathern mit o-standiger Alkylgruppe in Gegenwart von Bortrichlorid beobachtet wird (vgl.…”
Section: Neuerdings Hat Miller R361 Bei Der Einwirkung Von Methanolisunclassified
“…(10 hr.) (34). The 2,4,6-trichlorophenyl and p-nitrophenyl compounds were, however, stable under similar conditions.…”
Section: Ro-mentioning
confidence: 86%
“…; no yields were given and chlorinated by-products were claimed (123). More recently it ivas found that phenols react (equation 23) rapidly, exothermally, and nearly quantitatively with boron trichloride to produce stepwise dechlorination of the trichloride, and that the nature of the product depended upon the proportions in wrhich the reagents were mixed (33,34). In this respect there is marked resemblance between the phenols and alcohols, and differences in the two systems arise mainly out of the different behavior of the aryloxyboron chlorides and triaryl borates compared with their aliphatic analogs.…”
Section: Ro-mentioning
confidence: 99%
“…(130) at room temperature. Attempts to isolate mixed esters of boron have failed except for cyclic compounds (65) and certain o-nitrophenoxy esters (35) which have some feature stabilizing the mixed compound.…”
Section: B Group IIImentioning
confidence: 99%